PENGARUH BUDAYA DAN CITRA PERUSAHAAN TERHADAP KOMITMEN ORGANISASIONAL KARYAWAN - Syihabudhin, Syihabudhin (Jurnal Ekonomi Modernisasi, 2007)
Employees’ organizational commitment is behavior reflecting employees’ loyalty to the organization and continual process where employees express attention to the organization and success in reaching organization goals. Existence of organizational commitment is important for the organization, especially in tight business competition arena. The purpose of this research is to test and analyze the effect of corporate culture, and corporate image to the employees’ organizational commitment. Based on data from 162 non manager respondent, from 9 modern retail industry, by using analysis technique SEM in α = 0, 05, the research find that (1) company culture influence insignificantly to the employees’ organizational commitment of the modern retail industry sector employees, (2) corporate image affect significantly to the employees’ organizational commitment of the modern retail industry sector employees.